2017
DOI: 10.1038/s41598-017-08745-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (2001–2013) observations of water-soluble dicarboxylic acids and related compounds over the western North Pacific: trends, seasonality and source apportionment

Abstract: To better understand the impact of East Asian pollutants on the molecular composition of marine organic aerosols, we conducted long-term (2001–2013) observations of water-soluble dicarboxylic acids and related compounds in total suspended particulate samples collected at Chichijima Island in the western North Pacific (WNP). Seasonal variations of all the diacids and related compounds showed maxima in winter and spring and minima in summer, except for azelaic acid (C9), which maximized in summer to autumn. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 93 publications
4
36
0
Order By: Relevance
“…Their influence and contribution will be discussed in the following sections. The OC/EC ratios found in this study for the KV were similar to other sites in South Asia, like Lumbini (5.16 ± 2.09, 2.41-10.03; Wan et al, 2017), Delhi (5.86 ± 0.99, 2.9-9.2; Bisht et al, 2015), and Lahore (3.9 ± 1.6, 1.5-7.2; Alam et al, 2014).…”
Section: Major Ions Oc and Ecsupporting
confidence: 88%
See 2 more Smart Citations
“…Their influence and contribution will be discussed in the following sections. The OC/EC ratios found in this study for the KV were similar to other sites in South Asia, like Lumbini (5.16 ± 2.09, 2.41-10.03; Wan et al, 2017), Delhi (5.86 ± 0.99, 2.9-9.2; Bisht et al, 2015), and Lahore (3.9 ± 1.6, 1.5-7.2; Alam et al, 2014).…”
Section: Major Ions Oc and Ecsupporting
confidence: 88%
“…Field blanks (one blank filter each month) were also collected, briefly putting a filter onto the instrument without drawing air to assess potential contamination. There may be positive and negative artifacts during the sample handling/conditioning due to the adsorption/evaporation processes of organic aerosols (Li et al, 2018;Boreddy et al, 2017;Oanh et al, 2016). In a comparable study, Ding et al (2013) reported the positive artifacts for OC and organic tracers were 10 %-20 % and up to 16 %, respectively.…”
Section: Sample Collectionmentioning
confidence: 89%
See 1 more Smart Citation
“…4b). This result suggests an additional source of organic matter (completely independent of sea salt production and wind speed) which is evidenced by the higher MSA − / nss-SO 2− 4 mass ratios and higher concentrations of azelaic acid (Boreddy et al, 2017) during summer and autumn. MSA − / nss-SO 2− 4 mass ratios have been suggested as an indicator for the relative contribution of oceanic dimethyl sulfide (DMS) vs. anthropogenic sources to sulfate (Gondwe et al, 2004;Savoie and Prospero, 1989).…”
Section: Monthly/seasonal Variationsmentioning
confidence: 69%
“…Organosulfates (OSs), commonly formed via the interaction between VOC precursors and acidic sulfate seed particles, could be a potential source of "missing SOA" in current atmospheric models . OSs have been observed in various ambient atmospheres, including urban, rural, suburban, forest, and remote environments Meade et al, 2016;Stone et al, 2012;Riva et al, 2015;Brüggemann et al, 2017), which could represent 2-30 % of OA (Hawkins et al, 2010;Stone et al, 2012;Frossard et al, 2011;Tolocka and Turpin, 2012;Surratt et al, 2008;Liao et al, 2015).…”
mentioning
confidence: 99%